\( \angle E F G \) and \( \angle L M N \) are supplementary angles, \( m \angle E F G=(3 x+17)^{\circ} \), and \( m \angle L M N=\left(\frac{1}{2} x-5\right)^{\circ} \). \( m \angle E F G=\square^{\circ} \) \( m \angle L M N=\square^{\circ} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To find the measures of the angles, we start by using the property that supplementary angles add up to \(180^\circ\). Setting up the equation, we have: \[ m \angle EFG + m \angle LMN = 180 \] Substituting in the expressions for the angles: \[ (3x + 17) + \left(\frac{1}{2}x - 5\right) = 180 \] Combining like terms gives us: \[ 3x + \frac{1}{2}x + 17 - 5 = 180 \] \[ \frac{6x}{2} + \frac{1x}{2} + 12 = 180 \] \[ \frac{7x}{2} + 12 = 180 \] Subtracting 12 from both sides: \[ \frac{7x}{2} = 168 \] Multiplying both sides by 2 to eliminate the fraction: \[ 7x = 336 \] Now, divide by 7 to solve for \(x\): \[ x = 48 \] Now that we have \(x\), we can find each angle's measure. For \(m \angle EFG\): \[ m \angle EFG = 3(48) + 17 = 144 + 17 = 161^\circ \] For \(m \angle LMN\): \[ m \angle LMN = \frac{1}{2}(48) - 5 = 24 - 5 = 19^\circ \] Thus, we have: \( m \angle EFG = 161^{\circ} \) \( m \angle LMN = 19^{\circ} \)